Hypothesizing directional causality between the governance indicators and economic growth: The case of Afghanistan - Mohammad Naim Azimi; Mohammad Musa Shafiq (Future Business Journal, 2020)
This paper examines the causal relationship between governance indicators and economic growth in Afghanistan. We use a set of quarterly time series data from 2003Q1 to 2018Q4 to test our hypothesis. Following Toda and Yamamoto's (J Econom 66(1-2):225-250, 1995. https://doi.org/10.1016/0304-4076(94)01616-8) vector autoregressive model and the modified Wald test, our empirical results show a unidirectional causality between the government effectiveness, rule of law, and the economic growth. Our findings exhibit significant causal relationships running from economic growth to the eradication of corruption, the establishment of the rule of law, quality of regulatory measures, government effectiveness, and political stability. More interestingly, we support the significant multidimensional causality hypothesis among the governance indicators. Overall, our findings not only reveal causality between economic growth and governance indicators, but they also show interdependencies among the governance indicators.
Keywords: C01; K0; O4; 650; Causality; Corruption control; Economic growth; Governance; The rule of law